Investigation of cracking resistance of recycled Superpave mixtures - Gao, Ya (Kansas State University, 2017)
The use of economical and environmentally friendly recycled asphalt materials has become increasingly popular for asphalt pavement construction. Although reclaimed asphalt pavement (RAP) and recycled asphalt shingles (RAS) are typically used in hot-mix asphalt, increasing the amount of RAP and RAS materials increases the potential for premature pavement distresses, especially cracking. This research evaluated four recycled Superpave mixtures with different RAP and RAS contents from Kansas Department of Transportation projects. Two of the mixtures contained 10% RAP and 5% RAS, while the other two mixtures contained 25% RAP but no RAS. Illinois semicircular bending and Florida indirect tension tests were performed to assess mixture cracking and fracture properties. Results showed that mixtures containing 10% RAP and 5% RAS have relatively low fracture energy, creep compliance, energy ratio, and flexibility index but high resilient modulus. These results indicate that mixtures containing 10% RAP and 5% RAS are stiffer, more prone to cracking, and tend to absorb less fracture energy. Mixtures with 25% RAP and no RAS showed the opposite behavior.
Keywords: Asphalt; Cracking resistance; Recycled materials